5-2(3+x)=9(x-4)

Simple and best practice solution for 5-2(3+x)=9(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-2(3+x)=9(x-4) equation:


Simplifying
5 + -2(3 + x) = 9(x + -4)
5 + (3 * -2 + x * -2) = 9(x + -4)
5 + (-6 + -2x) = 9(x + -4)

Combine like terms: 5 + -6 = -1
-1 + -2x = 9(x + -4)

Reorder the terms:
-1 + -2x = 9(-4 + x)
-1 + -2x = (-4 * 9 + x * 9)
-1 + -2x = (-36 + 9x)

Solving
-1 + -2x = -36 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-1 + -2x + -9x = -36 + 9x + -9x

Combine like terms: -2x + -9x = -11x
-1 + -11x = -36 + 9x + -9x

Combine like terms: 9x + -9x = 0
-1 + -11x = -36 + 0
-1 + -11x = -36

Add '1' to each side of the equation.
-1 + 1 + -11x = -36 + 1

Combine like terms: -1 + 1 = 0
0 + -11x = -36 + 1
-11x = -36 + 1

Combine like terms: -36 + 1 = -35
-11x = -35

Divide each side by '-11'.
x = 3.181818182

Simplifying
x = 3.181818182

See similar equations:

| 16-6*2= | | a*3+5=10 | | 4x^3-12x^2-5=0 | | x^4+1.092=0 | | (5ab-b)+(7ab-12b)= | | 2abs(x-1)=abs(3x-4) | | (6xy+7x)(2x+5y)= | | -3+9-4= | | x-.13x=107000000 | | x+.13x=107000000 | | 4x^3+15x^4-4x=0 | | 2x^3-3x^2-12x+8=0 | | 8(x-0.5)-(3x-2)=5*1.3-1.5(11-6X) | | 2(5-6d)=7(d+9) | | 4(5a-3)=12 | | y-6x=24 | | x+(x+19)=89 | | 0.2(3x+3)=6(8x-3) | | 8x+56=0 | | 7-2a=-28+8a | | 10-2(2.5-13.5x)-6x=140-(11x+7) | | 7a+4=28-a | | 5464=656*296 | | -5a-7=28 | | 11-5y=2+y | | 7-a=-28+3a | | -3+2y=3-y | | 5a-7=-28 | | 6-2y=4-3y | | 7-a=28 | | 2(3+2x)=2 | | (1+y)dx=(1-x)dy |

Equations solver categories